Assessing of Customer Perception on Innovation of Food Service - Razak, Norfadzilah Abdul; Aminuddin, Zaidi Mohd; Ghazali, Ayu Rohaidah; Asnawi, Nini Hartini (Journal of Reviews on Global Economics, 2019)
In the highly competitive business environment, the restaurant industry critically strives to maintain their services particularly to customer's evaluation, changes in customer preferences and rapid of fast food and international restaurant that make business in Malaysia. As a local entrepreneur of the restaurant, they need several strategies to innovate their services to tackle their customer in highly competitive and make an improvement to another level standing with the international restaurant. Thus, a descriptive study was conducted to explore the perception of the customer towards several elements of innovation which are healthier food, modification of menu items, increase in food service options, technology advancement, environment sustainability, inclination towards global cuisines apply to one of the selected local restaurants. The survey was distributed to 235 of customers who walked into the restaurant and the finding revealed that healthier food, modification of menu items, food service options, technology advancement, environment sustainability inclination towards global cuisines and focus on customer of new generations are highly demand by the customers. The finding of this study also implies the effective practices that will be used in order to make an improvement, being creative and innovative of the restaurant product and services for the future.